Lean, agile and leagile healthcare management–A case of chronic care - Mishra V.; Samuel C.; Sharma S.K. (My University, 2025)
Healthcare services face a dual challenge of being lean and agile at the same time. This paper proposes an approach for implementation of leagility in healthcare services, especially chronic care like cardio-diabetes. The Multi-Dimensional Scaling method was used to visualize the dissimilarities among the selected inventory categories, which suggested us that selection of a supply chain strategy based on demand and lead time variability only, is not sufficient. Using focus group discussion additional factor influencing the strategy were determined and Analytical Hierarchy Process was used to find out the priority of these additional factors. Finally, a two-stage rule was developed to classify the categories into lean, agile and leagile groups. The study concluded that lean strategy is suitable for oral medicines, nursing- items and food supplements while leagile strategy is suitable for insulin, assistive –technologies, and diabetic footwear. The study appends Supply Chain Matrix proposed by Martin Christopher and proposes a more comprehensive method for implementation of leagile strategy in case of healthcare. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.